The effects of professional competency and the work motivation to the work performances of science teacher ( the survey of science teachers in junior high school ) - Galuh Catur Wisnu Prabowo (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
The performance is related to skill, competency behavior, knowledge and motivation. This study about surveying the relationship between professional competency, and motivation that teachers have to the work performances. Using path analysis, the survey results in there is a significant direct effect between professional competency to the work performed e as 28,2% and proved by tscore = 1.924 ttable = 1.686.  There is a significant direct effect between motivation and work performance as 39, 8% and proved by tscore = 2.179 ttable = 1.686. There is a significant direct effect between professional competency to the motivation as 38.7% and proved by tscore = 2.591 ttable = 1.686.  There is a significant indirect effect between professional competency to the work performed through the motivation with the value of path coefficient 0.154 or 15.4% and proved by tscore = 1.063 ttable = 1.687.